2019
DOI: 10.1017/s0022029919000542
|View full text |Cite
|
Sign up to set email alerts
|

Gain and loss of subcutaneous and abdominal fat depot mass from late pregnancy to 100 days in milk in German Holsteins

Abstract: This research paper addresses the hypothesis that in times of negative energy balance around parturition in dairy cattle, lipids stored in adipocytes are mobilised in a more intensive manner out of the abdominal depots than out of the subcutaneous adipose tissues. Furthermore, the impact of niacin supplementation and energy density of the ration on adipose tissue mass gain and loss was assessed. Absolute masses of subcutaneous (SCAT), retroperitoneal (RPAT), omental (OMAT), mesenterial (MAT) and abdominal adip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
13
3
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 34 publications
8
13
3
1
Order By: Relevance
“…These depot-specific differences could be modulated by differential extents of HSL phosphorylation between depots, observed in the present study and in previous work (Locher et al, 2011;Kenéz et al, 2015). Alternatively, this could be based on the fact that abdominal adipose depots provide a quantitatively greater fat pool, estimated to be approximately 3 times larger than subcutaneous fat depots (Raschka et al, 2016;Ruda et al, 2019).…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…These depot-specific differences could be modulated by differential extents of HSL phosphorylation between depots, observed in the present study and in previous work (Locher et al, 2011;Kenéz et al, 2015). Alternatively, this could be based on the fact that abdominal adipose depots provide a quantitatively greater fat pool, estimated to be approximately 3 times larger than subcutaneous fat depots (Raschka et al, 2016;Ruda et al, 2019).…”
Section: Discussionsupporting
confidence: 56%
“…Ji et al (2014) suggested that visceral adipose tissue might be more prone to release proinflammatory signals as an effect of overconditioning. Furthermore, ultrasonography-based predictions showed that abdominal adipose tissues (including retroperitoneal, omental, and mesenteric adipose tissues) together make up a roughly 3 times larger adipose mass than SCAT in German Holstein cows (Raschka et al, 2016;Ruda et al, 2019). Hence, abdominal adipose tissues, including RPAT, are suggested to have a larger contribution to adipose-derived nutrient metabolism than SCAT.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, RPAT had higher lipolytic activity than SCAT under catecholamine stimulation [12]. In contrast to SCAT, RPAT accumulated and lost adipose mass with greater uctuation during the peripartum period [13]. Collectively, these studies demonstrated that RPAT responds more dynamically to metabolic stimuli than SCAT, which is in agreement with human adipose biology [14].…”
Section: Introductionsupporting
confidence: 67%
“…The higher substrate in ux rate in RPAT could be supported by the greater dynamics of adipose mass, and higher HSL activity in bovine RPAT [23]. It was shown that the adipose mass of RPAT in periparturient German Holstein cows had a greater uctuation than that of SCAT [13,24]. Additionally, RPAT had a higher HSL phosphorylation at residues 563 and 660 detected by Western blot analysis, indicating greater enzyme activation [11].…”
Section: Backward Accumulation In the De Novo Synthesis Pathway In Rpatmentioning
confidence: 99%
“…Additionally, RPAT had higher lipolytic activity than SCAT under catecholamine stimulation [14]. In contrast to SCAT, RPAT accumulated and lost adipose mass with greater fluctuation during the peripartum period [15]. Collectively, these studies demonstrated that RPAT responds more dynamically to metabolic stimuli than SCAT, which is in agreement with human adipose biology [16].…”
Section: Introductionsupporting
confidence: 66%